QUALITATIVE ANALYSIS OF BANK DHOFAR SHRM INITIATIVE - Kolluru, Dr. Mythili; Kondaveeti, Mr. V.Ch. MadhuSudhana Rao; Balushi, Mrs. Sana Adbul Rahman Ali Al (The journal of contemporary issues in business and government, 2021)
Talent is a set of personal characteristics that enhance the performance of individuals.This study explores the effectiveness of the talent management program "Al Mawahib" in achieving the vision 2020 of Bank Dhofar. The bank has established its place as Oman's second-largest bank with 73 branches. Bank Dhofar launched a comprehensive strategic transformation plan that comprises various initiatives and projects. Bank Dhofar initiated the "Together 2020" the strategic transformation plan to meet the Vision 2020. The HR then developed a talent management program to support the organization objectives. The study traces the progress of the Al Mawahib talent development program. The study is qualitative research with an in-depth interview method with senior staff members. Content analysis was used to analyze the data from personal interviews. The study reveals that this program targets young and potential leaders. Linkage to the vision statement 2020 of Bank Dhofar is established. This program has trained 170 employees, who will train employees in their branches, which is the uniqueness of this program.